Gender Affirmation in India—The Current State of Knowledge, Management, Legal and Legislative Situation - Gupta, Richie (Indian Journal of Plastic Surgery, 2022)
A mismatch between the birth sex of a person and psychological recognition of self (gender) leads to a gender expression, which is at variance with the societal norms, and thus gives rise to gender incongruence (GI). In the past few years, there has been a significant change in demographics, understanding of etiology, management, laws and legislations in the field of GI. The authors, who have been performing gender affirmative surgeries (GAS) since the past 27 years, present their experience in gender affirmation together with the current state of knowledge. Recent studies report a significant rise in prevalence of GI, which is similar to the experience of author and other large volume Gender identity clinics in India and worldwide. This article endeavors to provide the medical professional with the current state of knowledge in the field of GI, so that they are better equipped to optimally manage these patients.
Keywords: gender incongruence; gender affirmation surgery; gender dysphoria; phalloplasty; vaginoplasty